Agile Development Conference
DOI: 10.1109/adevc.2004.9
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Rules: XP Experiences

Abstract: Agile processes such as XP (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Agility itself is defined by Highsmith and Cockburn (2001) as the "the ability to create and respond to change" (p. 120). Anecdotal evidence in the forms of lessons learnt and experience reports (Poole and Huisman 2001, Bedoll 2003, Rasmusson 2003, Jackson et al 2004, Schatz and Abdelshafi 2005, Coffin 2006, as well as several scientific studies (Fitzgerald et al 2006, Fruhling and De Vreede 2006, Sfetsos et al 2006, Dawande et al 2008, have argued for the appropriateness and effectiveness of various agile methods and practices. For example, in a theoretical analysis of pair programming (a common agile practice), Dawande et al (2008) found that pair programming will likely out-perform solo working when knowledge sharing between developers is efficient or when a scarce expert resource can be shared through pairing.…”
Section: Introductionmentioning
confidence: 99%
“…Agility itself is defined by Highsmith and Cockburn (2001) as the "the ability to create and respond to change" (p. 120). Anecdotal evidence in the forms of lessons learnt and experience reports (Poole and Huisman 2001, Bedoll 2003, Rasmusson 2003, Jackson et al 2004, Schatz and Abdelshafi 2005, Coffin 2006, as well as several scientific studies (Fitzgerald et al 2006, Fruhling and De Vreede 2006, Sfetsos et al 2006, Dawande et al 2008, have argued for the appropriateness and effectiveness of various agile methods and practices. For example, in a theoretical analysis of pair programming (a common agile practice), Dawande et al (2008) found that pair programming will likely out-perform solo working when knowledge sharing between developers is efficient or when a scarce expert resource can be shared through pairing.…”
Section: Introductionmentioning
confidence: 99%
“…A common problem for XP subjects conducted within universities is the lack of defined working hours [9]. The strategy we use to mitigate this problem is to emphasise that face-to-face teamwork is required and that teams must be able to schedule this.…”
Section: Teamsmentioning
confidence: 99%
“…Jackson, et al [9] list several factors which are likely to affect XP projects in universities. These include:…”
Section: B Xp In the Universitymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on quantitive value evaluation and cost estimation of requirements, optimizing methods are used to select suitable combinations from all requirements [14,15,18] for iterations. Recently, some researchers concentrate on the inconsistent requirements' value from multi-stakeholder viewpoints [17,19] and dependencies among requirements [20,21]. They suggest that the inconsistent value and dependencies should be considered when the optimizing methods are used.…”
Section: Related Workmentioning
confidence: 99%